The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/s1677-5538.ibju.2018.0143
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with prostate cancer and middle range prostate - specific antigen levels of 20 – 100 ng / mL

Abstract: Introduction: Prostate - specific antigen (PSA) is a useful biomarker for detection of prostate cancer (PCa) and for risk classification in addition to TNM classification and Gleason score (GS). We reported the role of PSA in patients with low (< 20 ng / mL) and extremely high (≥ 100 ng / mL) PSA levels. However, it is unclear whether a correlation exists between middle range PSA levels (20 – 100 ng / mL) at diagnosis and prognosis. Materials and Methods: Between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…The majority of patients with high initial PSA level reflects the severity of tumor characteristics or an asymptomatic tumor for a long period of time, indicating the possibility that the patient is neglectful of his condition [10]. A high PSA level also indicates a high androgen receptor activity of prostate cancer cells [11]. Previous studies also highlighted the mortality risk of a high PSA level [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients with high initial PSA level reflects the severity of tumor characteristics or an asymptomatic tumor for a long period of time, indicating the possibility that the patient is neglectful of his condition [10]. A high PSA level also indicates a high androgen receptor activity of prostate cancer cells [11]. Previous studies also highlighted the mortality risk of a high PSA level [12].…”
Section: Discussionmentioning
confidence: 99%
“…The differences of the findings in this study compared to previous studies may be due to the small number of samples in this study. Several studies suggested that a low TTC is due to PSA volume and PSA doubling time difference [11].…”
Section: Discussionmentioning
confidence: 99%
“…Even though this is the norm, certain patients have been noted to develop metastatic CaP at low PSAs. PSAs as low as 0.02ng/ml have been recorded in such patients and they are noted to have undifferentiated and very aggressive disease [24,25,26] Iwamoto and colleagues [27] in their study from 2000-2014 on 1873 patients had concluded that PSA is a useful biomarker for predicting prognosis at levels between 20 and 70 ng/ml. While Gleason's score is the single most important predictor of prostate cancer prognosis, the new grading system, known as the Grade Grouping System, better classifies CaP [28].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer had important modifications in diagnosis, clinical management and surgical treatment in last years (8)(9)(10)(11). Multiparametric magnetic resonance imaging (mpMRI) has become the standard of care and provides useful information for prostate cancer diagnosis (12).…”
Section: Editorial In This Issuementioning
confidence: 99%